Two cases of severe pneumonia after the 2011 Great East Japan Earthquake - Nakadate, Toshihide (World Health Organization, 2012)
In 2011, during the Great East Japan Earthquake and tsunami, 90% of victims died from drowning. We report on two tsunami survivors with severe pneumonia potentially caused by Legionella pneumophila. Both victims aspirated a large quantity of contaminated water; sand, mud and a variety of microbes were thought to have entered into their lower respiratory tracts. One patient had a mycotic intracranial aneurysm; the other patient had co-infections with several organisms, including Scedosporium species. Although scedosporiosis is a relatively rare infectious disease, symptoms are progressive and prognosis is poor. These pathogens are not specific for tsunami lung, but are reported causative agents for pneumonia after near-drowning.